Формування креативної компетентності студентів технічних спеціальностей у процесі викладання дисциплін фізико-математичного циклу - Дімітрова-Бурлаєнко, Світлана Дімова (Класичний приватний університет, 2017)
У статті обґрунтовано важливість креативності в здійсненні інженерної діяльності та необхідність формування креативної компетентності в студентів технічних спеціальностей. Розглянуто основні психолого-педагогічні підходи до розуміння поняття "креативна компетентність". Креативну компетентність конкретизовано як складне особистісне утворення, що охоплює сферу інтелекту, емоцій, моральних цінностей та уможливлює на принципово новому, інтегративному рівні перенесення набутих компетентностей з однієї галузі життєдіяльності в іншу з метою або досягнення принципово нового результату діяльності, або виконання діяльності на принципово новому якісному рівні. Для формування креативної компетентності в студентів технічних спеціальностей автор вважає за необхідне залучення до методичного арсеналу викладача спеціальних креативних технологій: методів психологічної активізації творчого мислення, систематизованого пошуку ідей, керованого пошуку ідей і розвитку творчої уяви тощо. Наведено приклади завдань, спрямованих на розвиток креативності, ініціативності, самостійності мислення студентів, використання яких є можливим у курсі загальної фізики та вищої математики в технічному університеті.

In the present article, the importance of creativity for performing the engineering activity and the need of formation of creative competence for students majoring in the technical sciences is justified. The main psychological and pedagogical approaches for understanding the concept of "creative competence" are considered. The author define the creative competence as a complex personal entity that covers areas of intelligence, emotions, moral values and, in an essentially new integrative level, enables transferring the acquired competences from one branch of the activity to another one with purpose either the achievement of essentially new results of the activity or the performance of the activity at an essentially new qualitative level. The formation of the creative competence of students is specified by the author as a process which forms and improves the mental operations such that analysis, synthesis, comparison and generalization, classification, planning and abstraction, and attempting to take a possession of them using the characteristics of critical thinking, depth, flexibility, latitude, speed, variability, as well as developing them through the imagination and assistance in knowledge acquisition of different contents. For this purpose, the author considers the necessary usage of special creative technologies in the methodical style of a lecturer such as methods of psychological activation of the creative thinking, directed to overcome psychological barriers, methods of the systematic search of ideas, which allow passing from a chaotic search to a system of the structured search of ideas, methods of the guided search of ideas and the development of the creative imagination aimed to override an inertia of thinking, and so on. In the paper, it is stated that the formation of creative competence of students majoring in the technical sciences is the most effective during teaching the physical and mathematical courses. The author gives examples of the tasks which are aimed with developing the creativity, initiative, independence of thinking of students, and the use of them is possible in the course of the general physics and the higher mathematics at a technical universities (research workshop including an experiment, creative tasks such as task-crosswords, tasks with conditions that contain an experiment, a paradox, data from other scientific areas, an analysis of literature or films, the compilation and selection of new tasks, etc.). The author emphasizes the importance of awakening the student’s desire for further development of creative opportunities because it promotes the formation of necessary professional qualities, which will be demanded in their further professional activity.
Formation of creative competence of students majoring in the technical sciences during teaching physical and mathematical courses
Keywords: креативність; технічна освіта; інженерна діяльність; навчальний процес; психолого-педагогічні дослідження; creativity; creative competence; students of technical specialties; educational process; engineering activities